EKSPRESI VERBAL SEBAGAI PEMBEDA GENDER DI SUKU SASAK DIALEK MENO-MENI DI KAMPUNG TENGARI REPOK, PRAYA, LOMBOK TENGAH: KAJIAN SOSIOLINGUISTIK - Hollysa Andini; Alpan Ahmadi (LPPM Institut Pendidikan Nusantara Global, 2022)
Languages ​​in this world have rules that accepted by all speakers in the form of spoken, written, and gestures that are solely used to communicate as social beings. Each language also has levels to choose diction or vocabulary in communicating. The level in question can be based on the social status of the community, economy, education and gender (gender). Moreover, gender was very decisive for the above. Verbal expressions related to gender was the object of research and the object of this research was one of the topics discussed in sociolinguistic studies. This study focuses on verbal expressions in the Sasak language and was used by the Sasak tribe with a dialect of meno-meni in the village of Tengari Repok, Praya, Central Lombok district. Therefore, the purpose of this study was to describe the verbal expressions in the Sasak language that differentiate or characterize and attach to a man or woman. The research instrument used in this study was interview and note-taking. The results showed that there were differences in verbal expression between men and women. Verbal expressions in this study was classified into several groups, namely: naming (genealogy), characteristics (differentiating / distinctive features), and philosophical.